Śeṣakr̥ṣṇa's Pārijātaharaṇacampū, a study - Sharma, Dipak Kumar (New Bharatiya Book Corporation, 1999)
Study of Pārijātacaraṇacampū of Kr̥ṣṇa, 16th cent., poem in mixed verse and prose (campū), on Krishna (Hindu deity).